Implant osseointegration in circumferential bone defects treated with latex-derived proteins or autogenous bone in dog's mandible - Manfrin Arnez, Maya Fernanda; Xavier, Samuel Porfírio; Pinto Faria, Paulo Esteves; Pedrosa Júnior, Wagner Fernandes; Cunha, Tatiana Ramirez; Mendonça, Ricardo José de; Coutinho-Netto, Joaquim; Salata, Luiz Antonio (Wiley, 2012)
Background: In sites with diminished bone volume, the osseointegration of dental implants can be compromised. Innovative biomaterials have been developed to aid successful osseointegration outcomes. Purpose: The aim of this study was to evaluate the osteogenic potential of angiogenic latex proteins for improved bone formation and osseointegration of dental implants. Materials and Methods: Ten dogs were submitted to bilateral circumferential defects (5.0×6.3mm) in the mandible. Dental implant (3.3×10.0mm, TiUnite MK3™, Nobel Biocare AB, Göteborg, Sweden) was installed in the center of the defects. The gap was filled either with coagulum (Cg), autogenous bone graft (BG), or latex angiogenic proteins pool (LPP). Five animals were sacrificed after 4 weeks and 12 weeks, respectively. Implant stability was evaluated using resonance frequency analysis (Osstell Mentor™, Osstell AB, Göteborg, Sweden), and bone formation was analyzed by histological and histometric analysis. Results: LPP showed bone regeneration similar to BG and Cg at 4 weeks and 12 weeks, respectively (p≥.05). Bone formation, osseointegration, and implant stability improved significantly from 4 to 12 weeks (p≤.05). Conclusion: Based on methodological limitations of this study, Cg alone delivers higher bone formation in the defect as compared with BG at 12 weeks; compared with Cg and BG, the treatment with LPP exhibits no advantage in terms of osteogenic potential in this experimental model, although overall osseointegration was not affected by the treatments employed in this study. © 2009 Wiley Periodicals, Inc.
Keywords: Bone regeneration; Circumferential bone defects; Hevea brasiliensis; Implant osseointegration; Latex proteins; angiogenic protein; latex; vegetable protein; angiogenesis; animal; blood clotting; bone regeneration; bone transplantation; comparative study; dog; drug effect; Hevea; male; mandible; methodology; oral surgery; tooth implantation; Alveolar Ridge Augmentation; Angiogenic Proteins; Animals; Blood Coagulation; Bone Regeneration; Bone Transplantation; Dental Implants; Dogs; Latex; Male; Mandible; Neovascularization, Physiologic; Osseointegration; Plant Proteins